Comparison of the effectiveness of autologous grafts for anterior cruciate ligament reconstruction: A protocol for an overview of systematic review and network meta-analysis. Issue 43 (23rd October 2020) - Jin, Jia-Xin; Fang, Peng-Zhong; Hu, Zhi-Wei; Chen, Jin-Lei; Wang, Rui-Rui; Wang, Xin
Abstract: Background: Anterior cruciate ligament rupture is a common motor system injury, and the most effective treatment is anterior cruciate ligament reconstruction (ACLR). Choosing the right graft is an important factor to ensure the success of the surgery. Current research shows that the clinical effect of autologous ligaments is better than that of allogeneic ligaments and artificial ligaments. However, there are differences between the autogenous ligaments, and how to choose them is still controversial. This study evaluated the published systematic reviews on the efficacy of different autologous ligament grafts in ACLR, and based on this, conducted a network meta-analysis of related randomized controlled trials. Methods: We searched 8 international and Chinese databases including PubMed, Embase, Web of Science, and Cochrane Library. The methodological quality of systematic reviews will be evaluated by Assessing the Methodological Quality of Systematic Reviews-2 (AMSTAR2) measurement tool. Cochrane's risk of bias tool will be used to assess the risk of bias of included randomized controlled trials, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach will be used to evaluate the evidence quality. Network meta-analysis will be applied to evaluate the therapeutic effect of different autologous grafts. The main outcome measures are IKDC score, clinical failure rate, Lachman test, Lysholm score, and the incidence of complications. Odds ratio and its 95% confidence interval will be used to synthesize the dichotomy results, while the mean difference and 95% confidence interval of continuous variables will be used for continuous variables. Results: This study will provide comprehensive evidence for the application of autologous grafts in ACLR. Conclusion: The results of this study will help clinicians make appropriate decisions. Protocol Registration number: INPLASY202090061.